(untitled) (Research, Society and Development, 2020)
Low power laser therapy is used as a medical and dental therapeutic resource, in order to enable its therapeutic effect on the body. Experimental tests on laboratory and animal models, with well-defined methodological criteria, suggest that low level laser therapy (LLLT - Low Level Laser Therapy) modulates several biological processes in animal models after being exposed to some trauma. This study aimed to evaluate the biomodulation of osteogenesis, using the infrared laser, in the skull cap of rats after making critical defects. The biological reactions of tissues submitted to laser were analyzed, comparing the intensity of bone neoformation, randomly distributed in four groups. Control groups (GC-I-II) did not receive a laser; the tests (GT-I-II) were treated with infrared laser, both at 2J / cm2 and at 90mW. Animal sacrifice and microscopic analysis, with HE staining, occurred in 07 and 21 days. The descriptive results showed that the groups irradiated with biomodulated laser positively affected the osteogenesis process, as they presented, at 07 and 21 days, a pattern of superior bone neoformation. The statistical analysis showed a superior bone neoformation score in both groups for 21 days, with larger areas of neoformation being observed. From the methodology used and with the radiation parameters used, in addition to the quantitative and histomorphometric descriptive results obtained in this research, it can be concluded that: LLLT can be used as an adjunct in the osteogenesis process in the repair of bone tissue. However, it is necessary to conduct clinical trials that prove its applicability.